Influence of different shading levels on growth and yield of kalmegh Andrographis paniculata Burm. f. (Nees) - Liphan, S.; Detpiratmongkol, S. (International Journal of Agricultural Technology, 2017)
Kalmegh Andrographis paniculata Burm. F. (Nees) is widely used as medicinal plant in Thailand to treat diseases such as sore throat, flu, fever, diarrhea and cough. Kalmegh production in some region is negatively affected by high radiation. However, the information on the effect of shade on growth and yield of Kalmegh is lacking. Thus, the objective of this study was to evaluate the effect of different shading levels on growth and yield of Kalmegh. The study was conducted during December, 2014 to April, 2015, at Faculty of Agricultural Technology, King Mongkut’ s Institute of Technology Ladkrabang, Bangkok. A split-plot in randomized complete block design with 3 replications was arranged. Four local Kalmegh varieties (Phisanulok 5-4, Prachinburi, Ratchaburi and Phichit 4-4) and 5 shading levels (0%, 20%, 40%, 50% and 80% of shading) were as main plots and sub plots, respectively. Data were collected on growth and yield of the crop. The results shown that we were not found interaction between Kalmegh varieties and shading levels. Prachinburi variety gave the highest number of branches plant-1, number of leaves plant-1, leaf area, shoot dry weight and leaf dry weight yield and followed by Ratchaburi, Phichit 4-4 and Phisanulok 5-4 varieties, respectively. Shading affected on growth and yield of Kalmegh. In addition, significant different were observed for all growth characters between open light condition (0% shade) and shaded plants. For different shading levels, leaves number plant-1, leaf area, shoot dry weight and leaf dry weight yield were the highest under 20% shading condition. It was concluded that Kalmegh variety Prachinburi performed better in terms of highest growth and yield grown under 20% shading condition.